Armut als Unrecht: Zur Aktualität von Hegels Perspektive auf Selbstverwirklichung, Armut und Sozialstaat - Schildbach, Ina (transcript, 2018)
As in Hegel's time, the functioning of bourgeois society today necessarily generates poverty – what are the causes of this problem?